You are on page 1of 2

1.

𝑦" − 9𝑦′ = 6𝑒 2𝑡 ; 𝑦(0) = 𝑦 ′ (0) = 0

Penyelesaian:

𝐿{𝑦" − 9𝑦′} = 𝐿{6𝑒 2𝑡 }

𝐿{𝑦" − 9𝑦′} = 6𝐿{𝑒 2𝑡 }


1
[𝑠 2 𝐿{𝑦} − 𝑠𝑦(0) − 𝑦 ′ (0)] − 9[𝑠𝐿{𝑦} − 𝑦(0)] = 6. 𝑠−2

1
[𝑠 2 𝐿{𝑦} − 0 − 0] − 9[𝑠𝐿{𝑦} − 0] = 6. 𝑠−2

1
𝑠 2 𝐿{𝑦} − 9𝑠𝐿{𝑦} = 6.
𝑠−2

1
(𝑠 2 − 9)𝐿{𝑦} = 6.
𝑠−2

6
𝐿{𝑦} = (𝑠−3)(𝑠+3)(𝑠−2)

1
𝐿{𝑦} = 6((𝑠−3)(𝑠+3)(𝑠−2))

𝐴 𝐵 𝐶
𝑦 = 6𝐿−1 {𝑠−3 + 𝑠+3 + 𝑠−2}

Maka dengan menggunakan metode pecah parsial didapat :


1 = 𝐴(𝑠 + 3)(𝑠 − 2) + 𝐵(𝑠 − 3)(𝑠 − 2) + 𝐶(𝑠 − 3)(𝑠 + 3)

1
𝑈𝑛𝑡𝑢𝑘 𝑠 = 2, 1 = −5𝐶 → 𝐶 = −
5

1
𝑈𝑛𝑡𝑢𝑘 𝑠 = −3, 1 = 30𝐵 → 𝐵 =
30

1
𝑈𝑛𝑡𝑢𝑘 𝑠 = 3, 1 = −6𝐴 → 𝐴 = 6

1 1 1

𝑦 = 6𝐿−1 { 6
} + 6𝐿−1 { 𝑠+3
30
} + 6𝐿−1 {𝑠−2
5
}
𝑠−3

1 6
1 −
𝑦 = 𝐿−1 {𝑠−3} + 𝐿−1 { 𝑠+3
5
} + 𝐿−1 {𝑠−2
5
}

1 1 1 6 1
𝑦 = 𝐿−1 {𝑠−3} + 5 𝐿−1 {𝑠+3} + − 5 𝐿−1 {𝑠−2}

𝟏 𝟔
𝒚 = 𝒆𝟑𝒕 + 𝒆−𝟑𝒕 − 𝒆𝟐𝒕
𝟓 𝟓
−3𝑡
2. 4𝑦" + 12𝑦′ + 9𝑦 = 24𝑡𝑒 2 ; 𝑦(0) = 0 ; 𝑦′(0) = 1

Penyelesaian :
−3𝑡
𝐿{4𝑦" + 12𝑦′ + 9𝑦} = 24𝐿{𝑡𝑒 2 }

1
4𝐿{𝑦"} + 12𝐿{𝑦′} + 9𝐿{𝑦} = 24 ( 3 )
(𝑠+ )2
2

1
4[𝑠 2 𝐿{𝑦} − 𝑠𝑦(0) − 𝑦 ′ (0)] + 12[𝑠𝐿{𝑦} − 𝑦(0)] + 9𝐿{𝑦} = 24 ( 3 )
(𝑠+ )2
2

1
4[𝑠 2 𝐿{𝑦} − 1] + 12[𝑠𝐿{𝑦}] + 9𝐿{𝑦} = 96 ((2𝑠+3)2 )

1
(4𝑠 2 + 12 + 9)𝐿{𝑦} = 96 ( )+ 4
(2𝑠+3)2

96 4
𝐿{𝑦} = (2𝑠+3)4 + (2𝑠+3)2

1 1
𝑦 = 96𝐿−1 { 3 } + 4𝐿−1 { 3 }
24 (𝑠+ )4 22 (𝑠+ )2
2 2

1 1
𝑦 = 6𝐿−1 { 3 } + 𝐿−1 { 3 }
(𝑠+ )4 (𝑠+ )2
2 2

3! 1!
𝑦 = 𝐿−1 { 3 } + 𝐿−1 { 3 }
(𝑠+ )3+1 (𝑠+ )1+1
2 2

𝟑 𝟑
𝒚 = 𝒆−𝟐𝒕 . 𝒕𝟑 + 𝒆−𝟐𝒕 . 𝒕